Investigating Factors that Influence Faculty Learning in Service Learning - Bandi, Surendra; Kandakatla, Rohit; Penta, Samyuktha (Proceedings from the International Research Symposium on Problem-Based Learning (IRSPBL), 2025)
Service-learning integrates community service with academic instruction, focusing on critical, reflective thinking and personal and civic responsibility. Faculty members engaged in service-learning often report significant professional and personal growth. However, understanding what specifically influences faculty learning in these settings is less explored. This research investigates the factors impacting faculty learning through service-learning, aiming to enhance educational strategies within engineering education. The study is taken up in a private university in India. The research question addressed in this study is - What are the factors that influence faculty learning in service-learning? This study aims to identify key elements that enable faculty learning. The target participants are the faculty who teach service-learning courses with community immersion experience. Qualitative study is used to collect the data. Data were collected through semi-structured interviews focusing on faculty experiences and perceptions. Thematic analysis of interviews with 20 faculty members who have participated in service-learning programs is carried out. The study identified several key factors influencing faculty learning in service-learning contexts. Service-learning contributes to faculty research opportunities, career advancement and enhanced teaching methodologies. Faculty reported that the scope of validating their experience in service-learning. This was by submitting articles in the conferences and journals of engineering education. Direct interactions with the community enhance faculty empathy towards societal issues. It was motivating them to integrate social responsibility into their teaching methods. Service-learning encourages faculty adopt various roles. They become innovators and problem solvers. They apply design thinking to real-world problems. Support from educational institutions helps faculty engagement and effectiveness in service-learning. The results indicate that service-learning influences faculty learning. The learning aspects are inculcating professional growth, enhancing empathetic understanding and encouraging innovative teaching approaches.